Ritual de formatura da Escola de Enfermagem de Manaus: representações objetais e significados para os egressos no período de 1955 - 2010. - (:unkn) unknown (Universidade Federal do Amazonas - Universidade do Estado do Pará, 2012)
This study is of a socio-historical nature, utilizing a qualitative approach which has as its ob-jective graduation ceremonies of the Nursing School of Manaus. The following objectives were delineated: to unveil the meaning of graduation ceremonies to the graduates who partici-pate in them, describe the object symbolism of the graduation ceremony and describe the changes which have occurred in graduation ceremonies, from the graduates‟ point of view. The time period within which this study is focused spans the years from 1955 to 2010. The primary sources utilized were, principally, photographs of graduations, in addition to written documents (the records of the ceremony) and interviews with graduates. A detailed analysis of the information took place using the BARDIN technique for content analysis. The results showed that, to graduates, graduation ceremonies mean victory, personal accomplishment, personal and professional achievement. Changes occurred in object symbolism principally with regard to garments, the justification being that the Nursing School of Manaus from 1955 to 1997 was administrated by the Special Service Foundation of Public Health – FSESP De-partment of Health and, in 1998, became part of the Federal University of Amazonas – UFAM administrated by the Department of Education. We concluded that analyzing the grad-uation ceremonies of the Nursing School of Manaus from 1955 to 2010 contributed to pre-serving for regional nursing the guiding light of our profession, showing the symbolic impact that traditions exert on the fields of health and education.
Keywords: ritual de formatura; história da enfermagem; enfermagem; graduation ceremonies; history of nursing; nursing; CIÊNCIAS DA SAÚDE: ENFERMAGEM